The addition of resection of the zygomatic arch in unilateral frontotemporoparietal decompressive craniectomy - Martin, Gerard Arvind (2013)
Decompressive craniectomy has long been uncontrollable intracranial pressure refractory to medical therapy. Since its inception at the beginning of the century, the procedure has seen many modifications and improvements in its technique, all the while adhering to the basic premise of achieving a reduction in intracranial pressure. This study presents a combination of principles, namely the addition of resection of the zygomatic arch to the parent procedure i.e. decompressive craniectomy, a concept borrowed from skull base techniques, which is adapted towards achieving this goal. Volumetric analysis using 3-Dimensional CT reconstruction techniques and measurements of CT metrics of brain expansion is utilized here to document any further increment in brain volume afforded by this maneuver. The objective of this study is to combine the resection of the zygomatic arch with standard decompressive craniectomy and the resulting increase in brain volume provided by the decompression was analyzed using 3D CT volumetric methods. Measurements of brain expansion metrics from CT images (Flint’s method) were also undertaken and analyzed. A prospective collection of patients suitable for the procedure was made after having met the required inclusion criteria, with a total of 21 patients undergoing decompressive craniectomy & resection of the zygomatic arch. Post-operatively, routine CT images were procured and the pre-operative and post-operative images were analyzed for volume and dimensional changes. Intracranial pressure (ICP) recordings and Glasgow Outcome Scale scores (GOS) were also documented for this study. Simultaneously, using the hospital electronic archiving system (PACS), a retrospective collection of CT images of patients previously operated in the same center was performed, and their pre and post operative images were similarly studied. The findings obtained from the two groups of patients were then compared and analyzed for statistical significance. Out of 21 experimental patients, 18 were deemed suitable for analysis. In the control arm, 29 patients were found to be suitable for analysis out of a retrospective collection of 38 patients. Volume analysis from 3D CT volumetric techniques revealed a further increase of 110.17 ml when compared with standard decompressive surgery and this was found to be statistically significant (p = 0.034). Concerning brain expansion metrics, analysis of maximum hemicraniectomy diameter revealed a mean of 13.17cm (p — 0.006). Analysis of the ratio of maximum hemicraniectomy diameter to maximum anteroposterior diameter gave a mean of 0.78 (p = 0.026) The addition of the zygomatic arch to standard decompressive craniectomy may prove efficacious in terms of absolute brain volume gain. This technique is comparable as opposed to other maneuvers done to provide maximum brain expansion in the immediate post operative period. However a prospective randomized study with a longer post operative observation period may still be required to further explore this significance.